Finding that marriage is not real and the relationship between the application of its consequences - KXurramova Adolat Bakhodir qizi; Tojibayev Akbar Zafar o’g’li (Zien Journals, 2022)
The article reflects the contradictions in family law related to the invalidation of marriage and its consequences, different approaches to the norms in practice and their solutions. Theoretical and practical issues related to the invalidation of marriage in the family law were analyzed on the basis of foreign legislation and their theories.
Keywords: Family; marriage; finding a fake marriage invalid; procedure for finding marriage invalid